Debating the Labour Movement’s Past, Present, and Future - Pollack, Marion; Selby, Jim (Labour / Le Travail, 2020)
The following is an exchange sparked by Jim Selby’s presentation piece in Labour/Le Travail vol. 83. Since debates about the labour movement’s strategies – past, present and future – raise important questions, we have printed Marion Pollack’s response to Selby’s article and, in keeping with journal protocol, his final response. —Editors' introduction